Guidelines for Space Utilization Based on Flood Disaster Mitigation in Residential Areas in South Balikpapan District, Balikpapan City - Pamungkas, Srirahadita; Suvana, Noermaya; Ariyaningsih, Ariyaningsih; Dewi, Dhyah Puspita; Kadri, Mohtana Kharisma (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2026)
South Balikpapan District is prone to flooding due to its location near the Ampal River basin, high land use density, and intense rainfall. This study aims to develop guidelines for flood mitigation-based spatial utilization in residential areas of South Balikpapan. Overlay analysis was used to determine flood vulnerability levels, and triangulation analysis to formulate spatial utilization guidelines. The results show that residential areas in South Balikpapan have high and moderate flood vulnerability. About 55% of the area, including Damai Bahagia, Damai Baru, Sepinggan, Gunung Bahagia, and Sungai Nangka (332.16 ha), are highly vulnerable, while 45% in Sepinggan Raya and Sepinggan Baru (157.33 ha) are moderately vulnerable. The proposed spatial utilization focuses on mitigation: prevention through relocation and infrastructure strengthening, handling via improved drainage and evacuation systems, and recovery through adaptive spatial planning. Integrating spatial utilization and flood mitigation is crucial for creating safe and sustainable residential areas.